Development of Pop-Up Book Learning Media Based on Canva for IPAS class IV SD Negeri 01 Sampiran - Yossi Dea Safitri (Postgraduate, University of Mataram, 2025)
This research is motivated by the limited learning resources available when learning takes place, especially in the IPAS subject matter in class IV SD Negeri 01 Sampiran. In learning, the class teacher usually only uses print media. Therefore, this study aims to: (1) describe the process of developing pop-up books learning media. (2) determine validity of pop-up books media. (3) determine effectiveness of pop-up books learning media on improving pupils learning outcomes. This type of research is research and development with the Borg and Gall model. This research is structured with eight stages consisting of potential and problems: data collection; product design; design verification; design revision; product trial; product revision; and trial use. The methods used in this research are tests, interviews, questionnaires, and document recording. Multiple-choice exams, questionnaires, and document recording sheets were the tools utilized to collect the data. Pop-up books learning resources powered by Canva has gone through several stages of media expert validation and material expert validation, with the result being